Mortality and Perception of Old Age. Conjectures Regarding the Argentine Case, 1850-1950 (Quinto Sol, 2018)
This article analyzes the way in which transition from mortality between 1850 and 1950 influenced perception of old age. To this end, it discusses classic measures of this phenomenon, it proposes new indicators based on probability of survival and it raises two main hypotheses. Firstly, the existence of a relationship between mortality and morbidity conditions by age and perception of old age. Secondly, the existence of a relationship between this one and the reduction in the universe of people relations, measured by proportions of widowhood and singleness by age and, to a lesser extent, of single person dwelling. This exploratory article combines systematic and exhaustive use of the four national population censuses, samples of the first two (1869 and 1895), mortality tables and qualitative information.
Keywords: mortality; survival; widowhood; old age; Argentina.